2020
DOI: 10.1155/2020/5152146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Type 2 Diabetes in Elderly Patients Aged 45-80 Years at Kanungu District

Abstract: Background. Type 2 diabetes is a worldwide disaster including in Uganda, specifically in Kanungu District which had a rise in diabetic patients in 2018/2019 as compared to the 2017/2018 financial year. This research was determined to access the prevalence and risk factors associated with type 2 diabetes on elderly patients aged 45-80 years attending Kanungu Health Centre IV, Kanungu District. Methods. A cross-sectional study was conducted among patients aged 45-80 years attending Kanungu Health Centre IV from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 10 publications
9
50
0
1
Order By: Relevance
“…A review study in Nigeria showed one of the risks factors for the pooled prevalence of DM was a family history of DM (4.6%; 95% CI 3.5-5.6) [40]. Other studies reported a family history of DM as a risk factor for contracting DM [41,42].…”
Section: Family Historymentioning
confidence: 99%
See 2 more Smart Citations
“…A review study in Nigeria showed one of the risks factors for the pooled prevalence of DM was a family history of DM (4.6%; 95% CI 3.5-5.6) [40]. Other studies reported a family history of DM as a risk factor for contracting DM [41,42].…”
Section: Family Historymentioning
confidence: 99%
“…Also, aging has been shown to induce a decrease in insulin sensitivity and inadequate response of β-cell functional mass and is also associated with a decrease of β-cell proliferative capacity [44,45]. Besides, studies in Africa have shown the association between increasing age and prevalence of DM [40,41,[46][47][48].…”
Section: Increasing Agementioning
confidence: 99%
See 1 more Smart Citation
“…As potential risk factors, well proved in the literature authors reported alcoholism, nicotinism, high bodymass index (BMI) and family history. (3) Diabetes mellitus may cause several different complications during course of the disease. One of the most common is peripheral neuropathy (DPN) causing damage to the peripheral sensory and motor nerves even in mild to moderate course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of family history for DM, overweight, and obesity increases the probability of acquiring type 2 DM. [ 5 ] The primary care plays a great role for DM and HTN and considered as one of the most effective strategy in reducing morbidity, disability, and premature mortality of both HTN and DM. [ 6 ] Investigating the impact of HTN and DM on the kidneys is important for health planners, clinicians, and academics.…”
Section: Introductionmentioning
confidence: 99%